Creative Economy Empowerment through the Use of Natural Ingredients to Become a Hand Sanitizer in Pager Gunung Singkup Pubaratu: Pemberdayaan Ekonomi Kreatif melalui Pemanfaatan Bahan Alami Menjadi Hand Sanitizer di Pager Gunung Singkup Pubaratu - Mardani, Dede Aji (Mattawang: Jurnal Pengabdian Masyarakat, 2020)
This service was conducted with the aim of providing illustrations and benefits of herbal plants, particularly betel leaf, lemongrass and lime for the manufacture of anti-septic fluids, specifically natural hand sanitizers. PAR (Participation Active Research) was used as the method applied in this study, which elaborated researchers with active participation of the community as partners and social research objects. The results of this study indicated that the liquid from the leaves and lime in clinical, medical and laboratory statistical tests has shown positive results with a pattern of killing germs and bacteria by 100%, it means that the more liquid contained in the solution, the more effective the solution in killing germs and bacteria. Abstrak Penelitian ini bertujan untuk memberikan ilustrasi dan manfaat dari tumbuhan herbal yaitu daun sirih, serai dan jeruk nipis untuk pembuatan cairan anti septik yaitu hand sanitizer alami. Metode yang digunakan adalah PAR ( Particiaption Active Research) yang mengelaborasikan peneliti dengan partisipasi aktif masyarakat sebagia patner dan objek peneltian sosial.hasil peneltian menunjukan bahwa cairan dari dedaunan dan jeruk nipis secara klinik, medis dan uji statistik laboratorium telah menunjukan hasil yang positif dengan pola membunuh kuman dan bakteri sebesar 100%, artinya semakin banyak cairan yang terkandung dalam larutan itu akan semakin efektif dalam membunuh kuman dan bakteri.